Effectiveness of Folic Acid Supplementation in Pregnancy on Reducing the Risk of Small-for-Gestational Age Neonates: A Population Study, Systematic Review, and Meta-Analysis. Issue 1 (March 2016) - Hodgetts, V.A.; Morris, R.K.; Francis, A.; Gardosi, J.; Ismail, K.M.
Abstract : ( BJOG. 2015;122(4):478–490) Being born small-for-gestational age (SGA) is associated with increased neonatal morbidity and mortality and with chronic illnesses later in life, including type 2 diabetes, obesity, hypertension, cardiovascular disease, and mental health problems. Therefore, prevention of SGA fetuses could produce significant public health benefits. Previous studies evaluating the effects of folic acid (FA) supplementation during pregnancy on birth weight have suggested an association between folate levels and absolute birth weight, but there is no indication of an effect of FA supplementation on reducing the risk of SGA.